PROJECT MANAGEMENT IN TECHNOLOGY: LESSONS LEARNED IN LEADING LARGE TEAMS - Bandeira Brasiliano, Bruno (Revista Gênero e Interdisciplinaridade, 2026)
This literature review focuses on project management in technology, emphasizing recent experiences in leading large, globally distributed teams. With the advent of hybrid methodologies and the need for integration between traditional and agile practices, new challenges and opportunities arise in the simultaneous management of multiple multinational projects and teams. This work seeks to critically analyze these challenges and the solutions implemented over the last five years (2019-2024), considering scientific articles and case studies published in recognized academic databases.